(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe and analyze the associations of anthropometric indices with the prediction of metabolic syndrome (MetS) among workers undergoing health check-ups at Hanoi Medical University Hospital. Methods: A cross-sectional study was conducted on 719 workers attending routine health examinations at Hanoi Medical University Hospital. Results: A total of 719 participants were included (54.9% women and 45.1% men). In both men and women, participants with MetS had significantly higher waist circumference, hip circumference, neck circumference, waist-to-height ratio (WHtR), waist-to-hip ratio (WHR), and body mass index (BMI) compared with those without MetS (p < 0.001). Multivariable logistic regression adjusted for age showed that all anthropometric indices were independently associated with the risk of MetS in both sexes, with generally stronger associations observed in men, particularly for waist circumference, neck circumference, WHtR, and BMI. Receiver operating characteristic (ROC) characteristic analysis demonstrated that waist circumference and WHtR were the most powerful predictors in both sexes, as reflected by high area under the curve values and large Youden indices, indicating their effective applicability in metabolic syndrome risk screening. Conclusion: Anthropometric indices, especially waist circumference and waist-to-height ratio, are strongly associated with and have high predictive value for metabolic syndrome in both sexes. Neck circumference is a simple and feasible screening measure that may aid in the early identification of metabolic syndrome risk in clinical practice.